Social Media’s Seductive Spell – Unraveling the Impact on Teen Girls - Manisha Singh Palawat; Gopal Singh Charan; Amanpreet Kaur; Shatrughan Pareek (Indian Journal of Social Psychiatry)
Body image is a critical aspect of a person’s mental and physical well-being. Social media platforms can provide opportunities to connect with peers, express themselves, and explore different identities. The prevalence of social media usage among teenage girls has raised concerns about the impact of sexualized images on their body image and well-being. The sexualization of social media and its impact on teen girls can be attributed to various factors. These factors such as peer comparison, peer influence, celebrity culture, cultural norms, social media algorithms, and advertising strategies play a significant role in promoting unrealistic beauty ideals. Therefore, it is crucial to thoroughly investigate and understand how these factors contribute to the issue. The negative impact of sexualized images includes internalization of beauty standards, negative body image, increased risk of eating disorders, psychosexual health issues, impaired mental health, and objectification of girls. To address this issue, several potential solutions and strategies are proposed. These include promoting digital literacy and critical thinking skills to help girls recognize the unrealistic nature of beauty standards portrayed on social media. Encouraging body positivity and diversity is essential to redefine beauty ideals. Open communication among parents, educators, and girls can create a supportive environment to discuss body image concerns. Mental health support and limiting social media exposure are crucial in mitigating the negative effects of sexualized images. Furthermore, the article emphasizes the need for government intervention to protect vulnerable users and encourage responsible platform management. Suggested policies and measures include age verification systems, robust content moderation, clear reporting mechanisms, and industry-wide guidelines for content and advertising.